Vibration analysis for a parallel fluid-filled pipelines-casing model considering casing flexibility. (1st October 2022) - Guo, Xumin; Cao, Yiming; Ma, Hui; Li, Hui; Wang, Bo; Han, Qingkai; Wen, Bangchun
Highlights: Ø A dynamic model of a PFFP-C considering casing flexibility is developed. Ø Vibration characteristics of the PFFP with and without casing flexibility are compared. Ø Vibration response of the PFFP under pulsation and displacement excitations is analyzed. Abstract: The dynamics research of fluid-filled pipelines in the general engineering field has received extensive attention. As the aero-engine pipeline is laid on the casing, the casing flexibility will inevitably affect the vibration state of pipelines. However, the previous investigations have not incorporated casing flexibility in the vibration analysis of aero-engine fluid-filled pipelines. Therefore, a dynamic model of a parallel fluid-filled pipelines-casing (PFFP-C) considering casing flexibility is developed by combining the semi-analytical method and improved transfer matrix method. The relationship between pipelines and casing is established through the flexible support of the casing and the displacement excitation transmitted from the casing to pipelines. The accuracy and significant computational advantage of the proposed model are verified by comparison with the response results of the ANSYS finite element model. The vibration responses of parallel fluid-filled pipelines with and without consideration of casing flexibility are compared. Besides, the frequency response of parallel fluid-filled pipelines under the combined action of fluid pulsation excitation and displacement excitation is also analyzed. The natural frequency and response amplitude of the fluid-filled pipelines have obvious differences after taking the casing flexibility into account, indicating that the influence of casing flexibility on the vibration characteristics of aero-engine pipelines is not negligible. This work can provide potential technical support and theoretical guidance for vibration analysis of aero-engine pipelines. Graphical abstract: Image, graphical abstract